Modification of radiative transfer model for estimating solar irradiance over Peninsular Malaysia - Yeap, Eng Choon (2014)
The availability of atmospheric parameters is important in estimating solar irradiance using Radiative Transfer Model. Atmospheric data such as temperature, relative humidity, pressure and atmospheric trace constituent in the function of altitude are the basic requirement for estimating solar irradiance and it is very limited. Static atmospheric model such as Air Force Geophysics Laboratory Atmospheric Constituent Profiles does provide the required parameter however it is outdated and does not reflect the local atmospheric condition. A Local Static Atmospheric Model for Malaysia was built in this study to provide the needed atmospheric parameters. The model was built based on monthly data from Atmospheric InfraRed Sounder in a period of ten years at peninsular Malaysia and validated with local meteorological data. Along with the atmospheric model, simple model of the atmospheric radiative transfer of sunshine was rewritten in MATLAB environment with some minor modification that allows the local atmospheric model to be integrated into the radiative transfer model. The modified radiative transfer model takes five parameters for the calculation of the solar irradiance which are, date, time, longitude, latitude and altitude. It reduces the parameter needed by the conventional radiative transfer model such as the inputs of atmospheric parameter, pressure, zenith angle, path length, and earth-sun distance. The modified the radiative transfer model was design to include the local atmospheric model as the main atmospheric input which improve its accuracy and suitable to be used locally. The results of the study were compared with the solar flux data from Aerosol Robotic Network which return an overall correlation of 97% with 4.8% root mean square error for zenith angle below 60°.